Increasing chlamydia screening tests in general practice: a modified Zelen prospective Cluster Randomised Controlled Trial evaluating a complex intervention based on the Theory of Planned Behaviour. (4th September 2013) - McNulty, Cliodna A M; Hogan, Angela H; Ricketts, Ellie J; Wallace, Louise; Oliver, Isabel; Campbell, Rona; Kalwij, Sebastian; O'Connell, Elaine; Charlett, Andre
Abstract : Objective: To determine if a structured complex intervention increases opportunistic chlamydia screening testing of patients aged 15–24 years attending English general practitioner (GP) practices. Methods: A prospective, Cluster Randomised Controlled Trial with a modified Zelen design involving 160 practices in South West England in 2010. The intervention was based on the Theory of Planned Behaviour (TPB). It comprised of practice-based education with up to two additional contacts to increase the importance of screening to GP staff and their confidence to offer tests through skill development (including videos). Practical resources (targets, posters, invitation cards, computer reminders, newsletters including feedback) aimed to actively influence social cognitions of staff, increasing their testing intention. Results: Data from 76 intervention and 81 control practices were analysed. In intervention practices, chlamydia screening test rates were 2.43/100 15–24-year-olds registered preintervention, 4.34 during intervention and 3.46 postintervention; controls testing rates were 2.61/100 registered patients prior intervention, 3.0 during intervention and 2.82 postintervention. During the intervention period, testing in intervention practices was 1.76 times as great (CI 1.24 to 2.48) as controls; this persisted for 9 months postintervention (1.57 times as great, CI 1.27 to 2.30). Chlamydia infections detected increased in intervention practices from 2.1/1000 registered 15–24-year-olds prior intervention to 2.5 during the intervention compared with 2.0 and 2.3/1000 in controls (Estimated Rate Ratio intervention versus controls 1.4 (CI 1.01 to 1.93). Conclusions: This complex intervention doubled chlamydia screening tests in fully engaged practices. The modified Zelen design gave realistic measures of practice full engagement (63%) and efficacy of this educational intervention in general practice; it should be used more often. Trial registration: The trial was registered on the UK Clinical Research Network Study Portfolio database. UKCRN number 9722.